Salt effects on the dilational viscoelasticity of surfactant adsorption layers. (February 2022) - Firouzi, Mahshid; Kovalchuk, Volodymyr I.; Loglio, Giuseppe; Miller, Reinhard
Abstract: Interfacial rheology of adsorbed layers of surfactants, demonstrating the response of the interface to interfacial deformations, plays a key role in formation and stability of foams and emulsions. It also provides insights into complex surfactant systems in different applications, in particular, medical treatments and diagnostics. The response of the interface is mainly determined by the composition of a surfactant system, the equilibrium and kinetic adsorption properties of the included surface-active compounds and their interaction within the adsorption layer. The subject of ongoing investigations is interfacial rheology of surfactant layers in the presence of inorganic ions. Although these ions have no surface activity, they can strongly influence the interfacial rheological properties owing to their interaction with the surface-active molecules. This work aims to present recent developments in the interfacial rheology of surfactant adsorbed layers at liquid–fluid interfaces in the presence and absence of salts, highlighting the state of the art of experimental and theoretical works in this area. We highlight drawbacks of recently developed techniques for measuring dilational interfacial properties of surfactant layers, compared with previous techniques. Moreover, this review shows the dearth of research on the ion-specific effect on the interfacial rheology of surfactant layers. This demonstrates the necessity of further investigation of the effect of ion specificity on interfacial viscoelasticity.